Extended finite element method - Zhuang, Zhuo (Oxford : Academic Press, 2014)
Extended Finite Element Method provides an introduction to the extended finite element method (XFEM), a novel computational method which has been proposed to solve complex crack propagation problems. The book helps readers understand the method and make effective use of the XFEM code and software plugins now available to model and simulate these complex problems. The book explores the governing equation behind XFEM, including level set method and enrichment shape function. The authors outline a new XFEM algorithm based on the continuum-based shell and consider numerous practical problems, including planar discontinuities, arbitrary crack propagation in shells and dynamic response in 3D composite materials. Authored by an expert team from one of China's leading academic and research institutionsOffers complete coverage of XFEM, from fundamentals to applications, with numerous examplesProvides the understanding needed to effectively use the latest XFEM code and software tools to model and simulate dynamic crack problems.
Chapter 9 -- X-FEM Simulation of Two-Phase Flows9.1 GOVERNING EQUATIONS AND INTERFACIAL CONDITIONS; 9.2 INTERFACIAL DESCRIPTION OF TWO-PHASE FLOWS; 9.3 X-FEM AND UNKNOWN PARAMETERS DISCRETIZATION; 9.4 DISCRETIZATION OF GOVERNING EQUATIONS; 9.5 NUMERICAL INTEGRAL METHOD; 9.6 EXAMPLES AND ANALYSES; 9.7 SUMMARY; Chapter 10 -- Research Progress and Challenges of X-FEM; 10.1 RESEARCH ON MICRO-SCALE CRYSTAL PLASTICITY; 10.2 APPLICATION OF MULTI-SCALE SIMULATION; 10.3 MODELING OF DEFORMATION LOCALIZATION; 10.4 SUMMARY; Appendix A -- Westergaard Stress Function Method.
Includes bibliographical references and index.
Online resource; title from PDF title page (ScienceDirect, viewed Apr. 14, 2014).
Keywords: Finite element method; MATHEMATICS -- Numerical Analysis; Finite element method; Electronic books